The Burden of Health Services Sector in Covid-19 Era - The Extent of Health Crisis in European Union and Innovative Solutions to Avoid A Major Health Crisis - Elena Iuliana PASCU-GABARA; Andrei CEPOI (Communications of International Proceedings, 2021)
The period of the SARS-CoV-2 pandemic was a crossroads that fundamentally changed the natural course of activity of all economic sectors worldwide, and healthcare sector was deeply influenced. This paper analyzes the relationship between the increased demand for health services during the pandemic and the limited supply of healthcare using the transversal method for some European Union(EU) states. The demand for health services is quantified by the main health indicators during the pandemic compared to the period before the pandemic, and healthcare is analyzed from the perspective of material and human resources. The findings indicate that, in most EU countries, there is a gap between the limited supply of healthcare and the magnitude of the demand for health services due to the SARS-Cov-2 infection. The results also suggest that in some countries, the gap is more significant than in other explained by the measures addressed by the competent authorities, cultural differences and education of the population. The authors investigate possible innovative solutions such as: artificial intelligence(AI) and robotic process automation(RPA) for triage systems, 3D-printing technology, healthcare wearables, flexible manufacturing systems and bid data analytics, the use of telemedicine, the scaling of Internet of Thing(IoT) that creates a centralized information system for monitoring and finally, the use of leadership trainings, courses and competences as a means to adapt fast to different situations. This paper is original because it examines the health crisis in EU and it proposes innovative solutions to prepare a health system to deal with major crises, such as the COVID-19 pandemic.
Keywords: Pandemic; Health Crisis; Robotic Process Automation Triage System; Bioprinting; Telemedicine.